Classifying Flash Flood Disasters From Disaster‐Prone Environments to Support Mitigation Measures - Zhai, Xiaoyan; Zhang, Yongyong; Zhang, Yongqiang; Liu, Ronghua; Liu, Changjun; Zhang, Xiaoxiang; Chen, Yuehong; Wang, Xiekang; Wright, Nigel (Water resources research, 2025)
Spatiotemporal heterogeneities in climatic, physiographic, and socio‐economic environments cause complex and varied formation mechanisms in flash flood disasters. However, previous studies were usually conducted at event or catchment scale in specific environments. Investigation on disaster formation mechanisms in climatic, physiographic, and socio‐economic environments with different combinations and quantities at large scale is not available, which further affects the decision‐making of mitigation measures. Our study develops a type‐based analytical framework of flash flood disasters and their causes from disaster‐prone environments using ten‐fold multivariate analysis including cluster analysis, analysis of similarities, and ordination analysis. Application of this framework to environment factors and losses of 37,332 disaster events across China revealed three disaster‐prone environment types, contributing 55.5% ± 0.3%, 55.9% ± 0.3%, and 50.9% ± 0.2% to variations in disaster attributes, respectively. The events with low disaster intensities (24.6%) in undeveloped northwestern China were governed by short rainfall, low retention capacity, and low prevention investments, and their mitigation focused on afforestation and construction of rainfall and flash flood monitoring systems. Those with high disaster intensities (38.5%) in developed and disturbed central and southeastern China were interpreted by frequent intense rainfall and good flood prevention infrastructures, and their mitigation prioritized development of flash flood forecasting warning models, and grain for green, etc. Those with intermediate disaster intensities (36.9%) in undeveloped southwestern and central China were shaped by frequent short intense rainfall and steep rivers, and their mitigation required satellites or radars in alpine regions, multi‐disaster prevention technology development, and dam construction. Plain Language Summary Flash flood disasters are one of the most dangerous natural disasters, and their formation mechanisms are influenced by the spatio‐temporal heterogeneities of climatic, physiographic, and socio‐economic environments. We develop a type‐based analytical framework of flash flood disasters and their causes from disaster‐prone environments. The framework and its robustness are applied and examined across China using massive flash flood disaster events and their environment factors. We discern three flash flood disaster‐prone environment types where 24.6%, 38.5%, and 36.9% of total flash flood disaster events have occurred during 1949–2019. We determine main causal factors and their contributions to shaping the attribute variability of flash flood disaster events for individual environment types, and further propose type‐specific measures to mitigate the occurrence and damage of flash flood disasters. This study provides a new insight for understanding flash flood disaster formation mechanisms, and provides supports for developing effective disaster management strategies. Key Points A type‐based analytical framework of flash flood disasters and their causes is proposed from disaster‐prone environments Three disaster formation types are derived through mining disaster‐prone environment factors and losses of 37,332 disaster events in China The variabilities of 50%∼56% in flash flood disasters are explained by the combinations of climate, physiography, and socio‐economy